A Study on Unmet Need of Contraception Among Married Women in Urban Field Practice Area of JJM Medical College, Davangere, Karnataka - Kashyap, Ritu; Vidya, G S; Dhar, Ruchi (National Journal of Community Medicine, 2017)
Background and Objectives: Unmet need of contraception is an on-going problem in India. The study was aimed to assess the unmet need of contraception and awareness of contraception among married women in the age-group of 15-49 years and reasons for non-usage of contraceptives among them. Methods: The study was a community-based cross-sectional study conducted among 180 married women in the age-group of 15-49 years. The sampling method used was systematic random sampling. A pre-tested questionnaire was used to collect data. Data entry was done in Epidata and analysed by SPSS v20.0. Results: The unmet need of contraception among study participants was17.2%; unmet need for spacing and unmet need for limiting was 7.8% and 9.4% respectively. Majority of them had awareness of copper-T (96.1%), condoms (94.4%), oral contraceptive pills (95.6%) and tubectomy (91.7%). The most common reason for non-usage of contraceptives was preference for male child (54.8%). Conclusions: The present study showed high unmet need of contraception among married women in the age group of 35-39 years with preference for male child as the most common reason for non-usage of contraceptives among them. Thus, there is a need to focus family planning services in this age-group of women with emphasis on gender equality.